2022
DOI: 10.3390/ma15113913
|View full text |Cite
|
Sign up to set email alerts
|

ORMOSIL Coatings Enriched with CeO2 (5-ATDT)-Ceramic Nanocontainers for Enhanced Protection of HDG Steel Used in Concrete

Abstract: This paper reports developing an innovative method of anticorrosion protection based on organically modified silica (ORMOSIL) enriched with CeO2 ceramic nanocontainers loaded with 5-amino-1, 3, 4-thiadiazole-2-thiol (5-ATDT) on hot-dip galvanized zinc (HDG) steel used to strengthen cement in concrete. The chemistry of ORMOSIL coatings and the production of CeO2 ceramic nanocontainers are described in detail for reproduction by other researchers. The anticorrosion properties of these novel coatings were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The anti-corrosion properties of these coatings were observed with electrochemical impedance spectroscopy (EIS) as a function of the exposure time. The EIS study showed that steel coatings exhibit the phenomenon of self-healing and protect the metal from corrosion [64,65].…”
Section: Microencapsulationmentioning
confidence: 99%
“…The anti-corrosion properties of these coatings were observed with electrochemical impedance spectroscopy (EIS) as a function of the exposure time. The EIS study showed that steel coatings exhibit the phenomenon of self-healing and protect the metal from corrosion [64,65].…”
Section: Microencapsulationmentioning
confidence: 99%
“…Derivatives of 1,3,4-thiadiazoles are widely used in coordination chemistry as ligands [42][43][44], in the synthesis of polymers [45], and the creation of polymer films [46,47]. The prospects of using 1,3,4-thiadiazoles in optoelectronics [48], in the purification of water from heavy metal ions [49], for the separation of minerals by the flotation method [50], and the creation of corrosion-resistant coatings [51] are discussed in the literature. A large number of works are devoted to the development of dyes and fluorescent markers based on 1,3,4-thiadiazoles [46,52,53].…”
Section: Introductionmentioning
confidence: 99%